Perancangan Kursi Ergonomi Pada Pekerja Bagian Finishing CV Abadi - Sokhibi, Akh; Alifiana, Mia Ajeng; Wisnujati, Andika; Susanto, Arief; Asri, Vikha Indira; Ariqi, Hafizh Lukman (Universitas Muhammadiyah Yogyakarta, 2021)
Design and redesign are some of the fields of study in ergonomics. The purpose of the design and redesign is to achieve comfort and increase productivity. Ergonomics is a science that integrates workers with the environment around them at work. So it is hoped that integration can be applied to all organizations. CV Abadi Jaya Presisi is a company engaged in the production of plastic, where workers carry out finishing stages without fulfilling ergonomic aspects. Namely, the use of a worker's chair made of plastic is not following the dimensions of the worker. The method used in this study is quantitative with anthropometric data as primary data. First, the anthropometric data of finished workers were used in this study. Then the data is tested for normality, uniformity test, and data adequacy test. After testing the data, the next step is to calculate the percentile value used to determine the size of the ergonomic chair to be designed. According to the findings of this study, the width of the chair is 42.1 cm, the height of the chair is 30.3 cm, the length of the chair is 43.2 cm, the length of the back of the chair is 49.9 cm, and the height of the seat elbow is 21.6 cm.